2015
DOI: 10.1093/abbs/gmv015
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a salt-tolerant cellulase from the mangrove oyster, <italic>Crassostrea rivularis</italic>

Abstract: A cellulase with wide range of pH resistance and high salt tolerance was isolated from the digestive gland of the oyster Crassostrea rivularis living in mangrove forests. The 27 kDa cellulase named as CrCel was purified 40.6 folds by anion exchange chromatography and extraction from the gel after non-reducing sodium dodecylsufate-polyacrylamide gel electrophoresis. The specific activity of the purified cellulase was 23.4 U/mg against carboxymethyl cellulose (CMC). The N-terminal amino acid sequence of CrCel wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
(49 reference statements)
1
12
1
Order By: Relevance
“…5A). When pre-incubated for 1 h at different temperatures, the enzyme showed more than 40% of residual activity until 70°C, demonstrating considerable thermal stability when compared with other purified cellulases [8]. The purified enzyme showed the best activity at pH 6.5 (Fig.…”
Section: Determination Of the Optimal Ph And Temperaturementioning
confidence: 90%
See 2 more Smart Citations
“…5A). When pre-incubated for 1 h at different temperatures, the enzyme showed more than 40% of residual activity until 70°C, demonstrating considerable thermal stability when compared with other purified cellulases [8]. The purified enzyme showed the best activity at pH 6.5 (Fig.…”
Section: Determination Of the Optimal Ph And Temperaturementioning
confidence: 90%
“…After that, the sample was washed in distilled water for equal time, followed by soaking the gel for 3 h at 60°C in 0.05 M acetate buffer (pH 6.5). Subsequently, the gel was stained with 0.1% Congo-Red dye for 30 min and the excess dye was removed by 1 M NaCl until the appearance of clear bands demonstrating that CMC was hydrolyzed, as previously described [8].…”
Section: Polyacrylamide Gel Electrophoresis Protein Weight Determinamentioning
confidence: 99%
See 1 more Smart Citation
“…Solubility is the primary property of protein isolates because of its significant influence on the other functional properties of proteins. However, protein isolates are seriously affected by endogenous enzymes in the process of pH‐shifting protein extraction, especially those in shrimp and shellfish, which are rich in endogenous enzymes (Sun et al ., 2014; An et al, 2015). Such effects are not conducive to production control and product stability.…”
Section: Introductionmentioning
confidence: 99%
“…Susan found that Mucor-originated L-asparaginase activity was unaffected by the addition of 4% (w/v) NaCl 70 . Tianchen showed that the activity of Cellulase was moderately improved in the presence of 0.5-1 M NaCl and when NaCl concentration was progressively increased up to 4 M, the activity remained unchanged 71 .…”
mentioning
confidence: 99%